In vivo evaluation of antimyotonic efficacy of β-adrenergic drugs in a rat model of myotonia - Desaphy, Jean-François (Pergamon Press, 2013)
The sodium channel blocker mexiletine is considered the first-line drug in myotonic syndromes, a group of muscle disorders characterized by membrane over-excitability. We previously showed that the β-adrenoceptor modulators, clenbuterol and propranolol, block voltage-gated sodium channels in a manner reminiscent to mexiletine, whereas salbutamol and nadolol do not. We now developed a pharmacological rat model of myotonia congenita to perform in vivo preclinical test of antimyotonic drugs. Myotonia was induced by i.p. injection of 30 mg/kg of anthracene-9-carboxylic acid (9-AC), a muscle chloride channel blocker, and evaluated by measuring the time of righting reflex (TRR). The TRR was prolonged from <0.5 s in control conditions to a maximum of ∼4 s, thirty minutes after 9-AC injection, then gradually recovered in a few hours. Oral administration of mexiletine twenty minutes after 9-AC injection significantly hampered the TRR prolongation, with an half-maximum efficient dose (ED(50)) of 12 mg/kg. Both propranolol and clenbuterol produced a dose-dependent antimyotonic effect similar to mexiletine, with ED(50) values close to 20 mg/kg. Antimyotonic effects of 40 mg/kg mexiletine and propranolol lasted for 2 h. We also demonstrated, using patch-clamp methods, that both propranolol enantiomers exerted a similar block of skeletal muscle hNav1.4 channels expressed in HEK293 cells. The two enantiomers (15 mg/kg) also showed a similar antimyotonic activity in vivo in the myotonic rat. Among the drugs tested, the R(+)-enantiomer of propranolol may merit further investigation in humans, because it exerts antimyotonic effect in the rat model, while lacking of significant activity on the β-adrenergic pathway. This study provides a new and useful in vivo preclinical model of myotonia congenita in order to individuate the most promising antimyotonic drugs to be tested in humans.